2000
DOI: 10.1897/1551-5028(2000)019<1311:baawnp>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity Associated With Noncoplanar Polychlorinated Biphenyls After Microbial Dechlorination of Aroclor 1242® and Aroclor 1254®

Abstract: Abstract-Bioremediation of polychlorinated biphenyls (PCBs) by anaerobic microbial dechlorination occurring naturally in the subsurface and in engineered systems results in mixtures of lower-chlorinated, primarily ortho-substituted biphenyls. The purpose of this study was to determine whether this process of bacterial dechlorination results in a mixture that differs in biological activity from that of the parent PCB mixture. Two biological assays sensitive to the action of ortho-substituted PCBs were employed:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The inability of microbial dechlorination to modify activity of commercial PCB mixtures on insulin secretion, neutrophil activation and splenocyte proliferation has been attributed to the presence of ortho-substituted PCB congeners with three or fewer chlorines (Ganey et al, 2000;Smithwick et al, 2004). Consistent with the latter report, structure-activity studies in our laboratory show that ortho-substituted di-and trichlorobiphenyls elicited increased uterine contraction frequencies of the magnitude similar to that observed with HR1260 (in preparation).…”
Section: Discussionsupporting
confidence: 80%
“…The inability of microbial dechlorination to modify activity of commercial PCB mixtures on insulin secretion, neutrophil activation and splenocyte proliferation has been attributed to the presence of ortho-substituted PCB congeners with three or fewer chlorines (Ganey et al, 2000;Smithwick et al, 2004). Consistent with the latter report, structure-activity studies in our laboratory show that ortho-substituted di-and trichlorobiphenyls elicited increased uterine contraction frequencies of the magnitude similar to that observed with HR1260 (in preparation).…”
Section: Discussionsupporting
confidence: 80%
“…For certain POPs, such as PCBs and selected organochlorine (OC) pesticides, primary releases in northern industrialized countries have effectively diminished, with atmospheric concentrations largely accounted for by continued (re)volatilization from contemporary reservoirs such as soil, vegetation, and water (e.g., refs 13-16). Given the gradual depleting processes for these persistent compounds through reactions with OH radical (17), hydrolysis (18), microbial action (19), and loss to the ocean floor (20)(21), then, assuming no further primary releases, atmospheric concentrations should be expected to decline; albeit, gradually over many years. Evidence of this is now apparent from several temperate studies, which have revealed reductions in atmospheric concentrations of PCBs (22,23).…”
Section: Introductionmentioning
confidence: 99%